GR Agonist Improves Responses in RA - Kuznar, Wayne (MD Conference Express, 2014)
The glucocorticoid receptor (GR) regulates genes that control development and metabolism and the immune response. A dissociated agonist of the glucocorticoid receptor (DAGR) is a nonsteroidal ligand of the GR that has both partial agonist and antagonistic properties. This article discusses a phase 2 trial that compared response rates between a DAGR and prednisone in patients with rheumatoid arthritis.